Socioeconomic status and oppositional defiant disorder in preschoolers: parenting practices and executive functioning as mediating variables - Granero, Roser; Louwaars, Leonie; Ezpeleta, Lourdes (Frontiers in Psychology, 2015)
Objectives. To investigate the mediating mechanisms of oppositional defiant disorder (ODD) in preschoolers through pathways analysis, considering the family socioeconomic status (SES) as the independent variable and the parenting style and the children’s executive functioning (EF) as the mediating factors. Method. Sample included 622 three years-old children from the general population. Multi-informant reports from parents and teachers were analyzed. Results. Structural Equation Modeling showed that children’s gender achieved a moderating role into the pathways valuing the underlying process between SES, EF, parenting style and ODD levels: a) for girls, the association of low SES and high ODD scores was mediated by parenting practices (punishment and inconsistent discipline) and by difficulties in EF inhibition, and a direct predictive effect on ODD level was achieved for SES, punishment and inconsistence in rearing style and inhibition; b) for boys, SES and EF (inhibition and emotional control) had a direct effect on ODD with no mediation. Conclusion. SES seems a good indicator to identify at high-risk children for prevention and intervention programs for ODD. Girls with ODD in families of low SES may particularly benefit from parent training practices and training in inhibition control.